2017
DOI: 10.1016/j.stemcr.2017.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Crohn's Disease Disturbs the Immune Properties of Human Adipose-Derived Stem Cells Related to Inflammasome Activation

Abstract: SummaryCrohn's disease (CD) is characterized by the expansion of mesenteric fat, also known as “creeping fat.” We explored the plasticity and immune properties of adipose-derived stem cells (ASCs) in the context of CD as potential key players in the development of creeping fat. Mesenteric CD-derived ASCs presented a more proliferative, inflammatory, invasive, and phagocytic phenotype than equivalent cells from healthy donors, irrespective of the clinical stage. Remarkably, ASCs from the subcutaneous depot of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 42 publications
5
60
0
Order By: Relevance
“…We observed that the expression of almost all of the genes tested was normalized to control levels in hASCs isolated from patients with inactive disease, indicating that immune system genes affected by methylation marks were for the most part partially restored in patients during episodes of remission. The exception to this was TNFA, whose expression remained high in patients during remission, which is in agreement with previous data [18].…”
Section: Immune Systemsupporting
confidence: 93%
See 3 more Smart Citations
“…We observed that the expression of almost all of the genes tested was normalized to control levels in hASCs isolated from patients with inactive disease, indicating that immune system genes affected by methylation marks were for the most part partially restored in patients during episodes of remission. The exception to this was TNFA, whose expression remained high in patients during remission, which is in agreement with previous data [18].…”
Section: Immune Systemsupporting
confidence: 93%
“…We found statistically significant differences in 18,253 CpGs between CD-and control-hASCs. To specifically evaluate the methylation patterns and the preferential genome location, we segmented all significant differentially methylated positions (DMPs) with a p value < 1 × 10 −4 into the following eight categories according to the Illumina annotations: transcription start site (TSS) 1500, TSS 200 (indicating the number of bases upstream), 5′ untranslated region (UTR), 1st exon, ExonBnd (exon boundary), gene body, 3′ UTR, and no gene location ( Fig.…”
Section: Differentially Methylated Positions In Adipose Stem Cells Ismentioning
confidence: 69%
See 2 more Smart Citations
“…The impact of donor age on MSC characteristics was demonstrated by Lo Surdo and colleagues, who showed that among MSC cell lines developed from eight donors, the cells from the oldest two donors had the lowest proliferative index and lowest colony‐forming unit percentage at P3. In terms of the patient's disease or condition, pioneering work from the laboratory of Vendrell showed that AD‐MSCs derived from the subcutaneous fat of patients with Crohn's disease exhibited an activated immune response and reduced immunosuppressive capabilities when compared to AD‐MSCs from healthy donors . On the other hand, allogeneic cells are derived from healthy and potentially younger donors, and the risk of rejection of the allogeneic MSCs by patients' immune cells is significantly minimized due to poor HLA Class I expression and absence of Class II expression by MSCs …”
Section: Discussionmentioning
confidence: 99%